Effect Of Alloying Elements On Microstructure And Properties Of Cast γ-TiAI Intermetallic Alloys. - Husni, Husni; M. Noor, Ahmad Fauzi; Astrawinata, Rizal (2005)

(untitled)
The effect of alloying elements on microstructure and properties of γ-TiAI based Intermetallic alloys produced by an in-house made arc-melting furnace was studied. The phases and microstructure of the produced alloys were characterized using X-Ray diffraction, and scanning electron microscope (SEM) respectively.